2015
DOI: 10.1186/s12873-015-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medical services transport delays for suspected stroke and myocardial infarction patients

Abstract: BackgroundPrehospital delays in receiving emergency care for suspected stroke and myocardial infarction (MI) patients have significant impacts on health outcomes. Use of Emergency Medical Services (EMS) has been shown to reduce these delays. However, disparities in EMS transport delays are thought to exist. Therefore the objective of this study was to investigate and identify disparities in EMS transport times for suspected stroke and MI patients.MethodsOver 3,900 records of suspected stroke and MI patients, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
3
11
3
4
Order By: Relevance
“…One study in Tennessee, USA, found that the prolongation of transportation time was influenced by seasons due to variations in traffic volume 23. However, transportation conditions are very different between Tennessee and Nara, which may explain in part the observed differences in results between these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Tennessee, USA, found that the prolongation of transportation time was influenced by seasons due to variations in traffic volume 23. However, transportation conditions are very different between Tennessee and Nara, which may explain in part the observed differences in results between these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Masalah yang ada di Kabupaten Banjar ini menjadi permasalahan tingkat nasional karena terbatasnya sarana dan prasarana, tingginya biaya perawatan dan perbaikan sarana transportasi, keterbatasan dana anggaran pemerintah yang tidak bisa ditangan oleh daerah (Meidiani, Malkhamah, & Muthohar, 2018). Berdasarkan riset sebelumnya menunjukkan bahwa transportasi yang lama mempengaruhi waktu untuk perawatan dan tujuan kesembuhan pasien (Golden & Odoi, 2015). Oleh karena itu dilakukan penelitian tentang transportasi pasien stroke ke intalasi gawat darurat rumah sakit.…”
Section: Pendahuluanunclassified
“…Proses tranportasi yang lambat tentu bisa menghambat untuk pertolongan pasien. Transportasi yang lama mempengaruhi waktu untuk perawatan dan tujuan kesembuhan pasien stroke (Golden & Odoi, 2015). Selain itu pekerjaan tentu kaitannya dengan sumber mata pencaharian.…”
Section: Metodeunclassified
See 1 more Smart Citation
“…Therefore, improvements in each and every part of prehospital assessment, for example, notification, activation, response, on-scene and transport intervals are public health necessities worldwide 3. However, due to the lack of adequate health budgets in many countries, particularly in low-income/middle-income ones, it is often difficult to allocate resources for a sufficient number of ambulances and paramedics.…”
mentioning
confidence: 99%